Síntese de monômero ácido alternativo para composição de sistemas adesivos autocondicionantes - Munchow, Eliseu Aldrighi (2014)
The aim of this study was to synthesize a new acidic monomer (polypropylene glycol methacrylate phosphorous Poly-P) to constitute an experimental two-step self-etch adhesive system and to evaluate its influence on the pH of different self-primers and on the microshear bond strength (μSBS) to enamel. Four experimental self-etch primers containing Poly-P (10, 15, 30 or 50 wt%), 2-hydroxyethyl methacrylate (HEMA), ethanol and water were formulated. A control primer (referential) and a commercial one (Clearfill SE Bond) were also used. The self-primers were allocated in two subgroups according to a buffered and a non-buffered pH. A microshear bond strength (μSBS) test protocol was performed at the enamel substrate, followed by the mechanical testing (EMIC). Scanning Electron Microscopy (SEM) was performed in the enamel surfaces after the self-primers application. The μSBS results were analyzed by One-Way Kruskall-Wallis test and Student-Newman-Keuls as post hoc test (p<0.05). As greater the Poly-P concentration, the lower the pH of the self-primers. The self-primers with a buffered pH resulted in the lowest μSBS values, while the non-buffered self-primers with Poly-P amount higher than 15 wt% showed the highest bond strength results, and similar to the control/referential adhesive systems used. The SEM images demonstrated that the self-primers with high Poly-P content (30 and 50 wt%) resulted a Type 1 etching pattern in the enamel surface. The pH of the self-primer was directly influenced by the acidic monomer concentration, which has directly affected the enamel bond strength results. The Poly-P is a potential monomer to be used in the formulation of self-etch dental adhesive systems